Iscador Qu inhibits doxorubicin-induced senescence of MCF7 cells. Issue 1 (December 2017) - Srdic-Rajic, Tatjana; Santibañez, Juan; Kanjer, Ksenija; Tisma-Miletic, Nevena; Cavic, Milena; Galun, Daniel; Jevric, Marko; Kardum, Nevena; Konic-Ristic, Aleksandra; Zoranovic, Tamara
Abstract Chemotherapy in patients with inoperable or advanced breast cancer inevitably results in low-dose exposure of tumor-cell subset and senescence. Metabolically active senescent cells secrete multiple tumor promoting factors making their elimination a therapeutic priority. Viscum album is one of the most widely used alternative anti-cancer medicines facilitating chemotherapy tolerance of breast cancer patients. The aim of this study was to model and investigate howViscum album extracts execute additive anti-tumor activity with low-dose Dox using ER + MCF7 breast cancer cells. We report that cotreatment of MCF7 withViscum album and Dox abrogates G2/M cycle arrest replacing senescence with intrinsic apoptotic program. Mechanistically, this switch was associated with down-regulation of p21, p53/p73 as well as Erk1/2 and p38 activation. Our findings, therefore, identify a novel mechanistic axis of additive antitumor activity ofViscum album and low dose-Dox. In conclusion, ER + breast cancer patients may benefit from addition ofViscum album to low-dose Dox chemotherapy due to suppression of cancer cell senescence and induction of apoptosis.